2021
DOI: 10.1093/ejo/cjab055
|View full text |Cite
|
Sign up to set email alerts
|

Scandcleft randomized trials of primary surgery for unilateral cleft lip and palate: comparison of dental arch relationships and dental indices at 5, 8, and 10 years

Abstract: Summary Background and trial design The Scandcleft intercentre study evaluates the outcomes of four surgical protocols (common method Arm A, and methods B, C, and D) for treatment of children with unilateral cleft lip and palate (UCLP) in a set of three randomized trials of primary surgery (Trials 1, 2, and 3). Objectives To evaluate and compare dental arch relationships of 5-, 8-, and 10-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
(58 reference statements)
0
5
0
1
Order By: Relevance
“…However, no significant differences between dental arch relationships between Arms A and C have been found in Trial 1 at 5, 8, and 10 years. 39…”
Section: Previous Surgical Treatment and Need For Additional Treatmentmentioning
confidence: 99%
“…However, no significant differences between dental arch relationships between Arms A and C have been found in Trial 1 at 5, 8, and 10 years. 39…”
Section: Previous Surgical Treatment and Need For Additional Treatmentmentioning
confidence: 99%
“…The disease causes great mental and financial stress to the children and their families [ 24 ]. At present, there is limited methods for prenatal prevention and the outcome of surgical treatment is not satisfied [ 25 , 26 ]. Studies have shown that LncRNA is widely involved in cell differentiation, metabolism, and proliferation, and closely related to a variety of diseases [ 19 , [27] , [28] , [29] ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent randomised controlled study did not find any statistically significant difference in DAR outcomes between EPR with the hard and soft palates repaired at 3–4 months and DPR in which the hard palate closure was postponed to 12 or 36 months. No data were reported for the PM because the authors did not find the parameter to be acceptably reliable [ 42 ]. Stein et al observed a similar palatal height but a smaller transverse distance in the upper anterior arch following EPR which tended to compensate at the ages of 15 to 18 years, reaching values comparable to DPR [ 43 ].…”
Section: Discussionmentioning
confidence: 99%